1985
DOI: 10.1128/jvi.54.2.623-624.1985
|View full text |Cite
|
Sign up to set email alerts
|

A candidate for a new serotype of human rotavirus

Abstract: We investigated genetic and serological characteristics of a human rotavirus isolate from Indonesia which had a "super short" RNA electrophoretic pattern (A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
86
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(90 citation statements)
references
References 6 publications
4
86
0
Order By: Relevance
“…Group A HRVs are responsible in most cases, whereas the epidemiological role of group B and C HRVs has not yet been clearly determined [Bridger et al, 1986;Nakata et al, 1987;Burns et al, 19891. Human and animal group A RV strains possess a common group antigen, VP6 (the gene 6 product), located in the inner viral capsid, which also contains determinants responsible for subgroup specificity [Kalica et al, 1981;Greenberg et al, 1983al. To date, six distinct HRV serotypes, including the four established serotypes 1-4 [Hoshino et al, 19841, and the two new serotypes 8 [Matsuno et al, 1985;Albert et al, 1987bl and 9 [Clark et al, 19871, have been reported. The different serotypes have been identified on the basis of their reactivity with animal hyperimmune sera in neutralization assays.…”
mentioning
confidence: 99%
“…Group A HRVs are responsible in most cases, whereas the epidemiological role of group B and C HRVs has not yet been clearly determined [Bridger et al, 1986;Nakata et al, 1987;Burns et al, 19891. Human and animal group A RV strains possess a common group antigen, VP6 (the gene 6 product), located in the inner viral capsid, which also contains determinants responsible for subgroup specificity [Kalica et al, 1981;Greenberg et al, 1983al. To date, six distinct HRV serotypes, including the four established serotypes 1-4 [Hoshino et al, 19841, and the two new serotypes 8 [Matsuno et al, 1985;Albert et al, 1987bl and 9 [Clark et al, 19871, have been reported. The different serotypes have been identified on the basis of their reactivity with animal hyperimmune sera in neutralization assays.…”
mentioning
confidence: 99%
“…In this retrospective analysis, serotype G8 was shown to be the predominant bovine rotavirus G type in the Higley, Arizona area during the 1974-1975 season. Serotype G8 virus was first recovered from a child with gastroenteritis in Indonesia in 1984 [29,43]; the first bovine G8 strain was isolated in Scotland in 1984 also [47,62]; later it was detected in North America and other countries [18,19,41,49,52,65]; and appears to be epidemiologically important today in parts of Africa [59]. Various reports [18,24,49,62] appear to indicate that G8 is one of the less common serotypes among bovine rotaviruses, however, the G8 has been reported to be the predominant G type in cattle in some parts of the world during certain periods of time [15,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…The medical importance of the non-group A rotaviruses in human diarrhoeal illness remains to be determined. To date, at least five serotypically distinct human rotaviruses have been isolated (3).…”
Section: Introductionmentioning
confidence: 99%